PERAN REPRESENTASI MATEMATIS DALAM PEMBELAJARAN PERKALIAN BENTUK ALJABAR MELALUI PENDEKATAN MATEMATIKA REALISTIK - Jupri, Al; Usdiyana, Dian; Sispiyati, Ririn (Universitas Hamzanwadi, 2020)
Algebra is an abstract topic in mathematics that should initially be learned by students in junior high school level. In order that this topic is easier to understand by students meaningfully, relevant mathematical representations should be used in the learning process. This research aims to analyze the role of mathematical representations in the learning of multiplication of algebraic expressions through the use of realistic mathematics education approach. To do so, we used a qualitative research method, in the form of the learning and teaching process involving 23 grade VII students (12-13-year-old) from one of the schools in Bandung. We analyzed video data of the learning process and the student written work from a formative test. The results showed that visual representations are frequently used by students at the beginning of the learning process and symbolic representations are used after the students get used to using visual representations. The result of the formative test indicated that the use of mathematical representations meaningfully could help students in solving multiplication of algebraic expressions problems. We conclude that the use of mathematical representations?in particular of visual representations using geometry context in algebra learning?helps students to understand the topic of multiplication of algebraic expressions.